The ciberdefense and its legal regulation in Argentina (2006 - 2015) - Cornaglia, Silvina; Vercelli, Ariel Hernán (FLACSO - Sede Ecuador, 2017)
The article analyzes the place and how cyberdefense was developed within the defense system of República Argentina. To this end, the norms that have been produced on the subject during 2006 - 2015 are relieved and analyzed. The study shows that two institutions have been the most active: on one hand, stand out the regulations of the Ministerio de Defensa, and, on the other, the regulations of the Jefatura de Gabinete de Ministros. The research has a double purpose. Firstly, to favor a greater level of legislative systemacy in cyberdefense. Second, to produce substantive information for the elaboration of public policies and regional collaboration activities. The article is part of a larger investigation focused on the analysis of the different ways of regulating cyberspace.